Advances in stallion's epididymal sperm technology - Melo, Cely M. (2010)
Freezing epididymal sperm is a method to preserve germplasm from animals with not only high genetic potential but also endangered species. In the equine some owners have chosen this possibility in cases of either severe illness or death of stallions. However, the lack of knowledge and poor published results of such technique hampers its propagation. New procedures have allowed some improvement on fertility rates of frozen sperm from the epididymis of stallions. The aim of this study is to report the advances on processing and cryopreservation of samples from the stallion's epididymal semen.